Adherence to the Mediterranean Diet in Cyprus and its relationship to Multi-Morbidity: An epidemiological study - Kyprianidou, Maria; Panagiotakos, Demosthenes B.; Faka, Antigoni; Kambanaros, Maria; Makris, Konstantinos C.; Christophi, Costas A. (My University, 2021)
Objective To examine the adherence to the Mediterranean diet in the adult general population of Cyprus and assess its relationship with multi-morbidity. Design A representative sample of the adult population of Cyprus was selected in 2018-2019 using stratified sampling. Demographics, Mediterranean diet, smoking, and physical activity, as well as the presence of chronic, clinical, and mental conditions were collected using a validated questionnaire. Diseases were classified according to the International Classification of Diseases, 10th Revision (ICD-10). Setting The five government-controlled municipalities of the Republic of Cyprus. Participants A total of 1140 Cypriot men and women over 18-year old. Results The average Mediterranean Diet score was 15.5 ± 4.0 with males and residents of rural regions being more adherent to the Mediterranean Diet compared to females and residents of urban regions respectively (p<0.05). Being in the higher tertile of adherence to the Mediterranean diet was associated with lower odds of multi-morbidity compared to the lower tertile and this result was statistically significant even after adjusting for age, gender, smoking habits, and physical activity (OR= 0.68, 95% CI: 0.46, 0.99). Conclusions The study provides evidence of the adherence to Mediterranean diet in Cypriot population and its association with multi-morbidity. Adherence to the Mediterranean diet was associated with lower risk of multi-morbidity. Future research would attempt to replicate such results that could add solid pieces of evidence towards meeting some criteria of causality and severity tests, hence prevention programs and practice guidelines in Cyprus and elsewhere should take into account those beneficial effects.
Keywords: Chronic diseases; Epidemiology; Mediterranean diet; Multimorbidity; Nutrition